Rupture of a basilar trunk aneurysm in the postoperative period of clipping of a Sylvian aneurysm - Benedek, Pedro; De Tenyi, Andrés; Purriel, Juan; Pol Deus, Jorge; Reyes Cibils, José; Borges de Medeiros, Juares (Cirugía del Uruguay, 1979)
An unfrequent case of rupture of a basilar artery aneurysm three days after successful clipping of a middle cerebral artery aneurysm is presented. Death occured due to massive intraventricular hemorrhage by perforation of the floor of the III ventricle.